Estudo da protoporfirina IX como marcador fluorescente da aterosclerose - Silva, Monica Nascimento da [UNIFESP] (2014)
Atherosclerosis is a chronic degenerative disease characterized by the presence of injuries with aspects of plaques or atheromas in arteries of medium and great caliber. It is the primary cause of cardiovascular disease and stroke, that in turn represent the main cause of death for disease in the world. This study searches a potential atherosclerosis biomarker that it can make possible a minimum invasive diagnostics method and of low cost. In this study 29 rabbits of the race New Zeland had been separate in two main groups: the Control Group, where the animals had received normal diet and the Experimental Group, where the animals had received hypercholesterolemic diet (1% of cholesterol). In a first study blood was collected and liver and arteries were extracted. A metabolic profile of rabbits was made after 22, 43 and 64 days of the beginning of the diet. The excised arteries had been analyzed by microscopy for verification of the installation of the atherosclerotic process in the rabbits of 0 the 64 days. In a second experiment the rabbits had been followed up to 89 days after the beginning of the diet. In this study the blood was collected each 20 days and excrements weekly. Our objective was to verify of the variations of the amount of porphyrin extracted with acetone, in the blood and excrements, with the atherosclerosis stage. With excrements a calibration curve for the determination of the best amount of fecal mass for optimum volume of acetone was gotten, for the extraction of the coproporphyrin. Optimum result was gotten with 0,10 g of fecal mass for 400 µL of acetone. For the group 89 days it had the administration of amminolevulinic acid, or ALA, before and after the blood collection. The study with ALA was continued in one third and last experiment with rabbits. The study of the porphyrin extraction showed the increase of porphyrin fluorescence as in the blood as in excrements in the group of the hypercholesterolemic diet induction, following the increase of the values of LDL (lipoprotein of low density) and the increase of the atheroma. Already the use of the ALA, resulted in an increase in the of the protoporphyrin IX (PPIX) emission signal in the blood of the experimental group in relation to the control group. This study identified a potential marker of atherosclerosis.